2017
DOI: 10.1007/s10620-017-4579-x
|View full text |Cite
|
Sign up to set email alerts
|

Direct Downregulation of B-Cell Translocation Gene 3 by microRNA-93 Is Required for Desensitizing Esophageal Cancer to Radiotherapy

Abstract: Direct downregulation of BTG3 by miR-93 is able to render ESC resistant to radiotherapy, and both BTG3 and miR-93 may potentially serve as clinical markers for ESC and contribute to the treatment of ESC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Also, we further demonstrated that HOTAIR loss enhanced IR-mediated anti-tumor effects in CRC xenograft tumors. MiR-93, a member of miR-106b~25 cluster 28 , has been found to be closely linked with tumor initiation, progression, and radioresistance in some malignancies [29][30][31] . Also, previous studies showed that miR-93 could function as a negative regulator of cell autophagy 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, we further demonstrated that HOTAIR loss enhanced IR-mediated anti-tumor effects in CRC xenograft tumors. MiR-93, a member of miR-106b~25 cluster 28 , has been found to be closely linked with tumor initiation, progression, and radioresistance in some malignancies [29][30][31] . Also, previous studies showed that miR-93 could function as a negative regulator of cell autophagy 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Various miRNAs have been reported to be aberrantly expressed in a number of different types of human cancer, including miR-144 (3,29,31). miR-144 has been widely researched and reported to be an important regulator of tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, we have witnessed a remarkable decrease in the incidence rate of cervical cancer due to the powerful tools in diagnosis and further therapy of this disorder [123,124]. B cell translocation gene 3 (BTG3) inhibition is a promising strategy by tumor cells to decrease the efficacy of radiotherapy [125]. Moreover, BTG3 is considered as a tumor suppressor and its inhibition enhances the malignancy of cervical cancer cells [126].…”
Section: Cervical Cancermentioning
confidence: 99%
“…MiR-93 enhances the malignancy and proliferation of glioblastoma cells by inhibition of autophagy via down-regulation of Beclin-1, ATG5, and ATG4B [106] EC cells Oncogenesis Reducing the capability of radiotherapy by inhibition of BTG3 [125] HeLa and C-33A cells cervical cancer tissues Oncogenesis LncRNA ZNF667 suppresses the invasion and malignancy of cancer cells by inhibition of miR-93-3p [311] Cisplatin-resistant A2780/DDP cell line Oncogenesis Inhibition of miR-93 by l-tetrahydropalmatine is beneficial in sensitizing of cancer cells to cisplatin-mediated apoptosis [312] Bladder cancer tissues and cells Oncogenesis Upregulation of miR-93 is related to the tumor stage and node stage via stimulation of PEDF [313] Cervical cancer and matched non-cancerous tissue samples…”
Section: Glioblastoma Cells Oncogenesismentioning
confidence: 99%